Spatio-temporal evolution and influencing factors of net carbon sink in marine aquaculture in China - Guan, Hongjun; Sun, Zhenzhen; Zhao, Aiwu (Frontiers in Environmental Science, 2022)
The carbon storage cycle of marine cultured shellfish and algae is long. In particular, the carbon sequestration time of shellfish can reach thousands of years, which is much higher than that of terrestrial green carbon ecosystems such as forests. Therefore, marine aquaculture not only has considerable economic benefits, but also provides high-quality "decarbonization space" for carbon neutrality. Using the two-stage LMDI (logarithmic mean division index) method, this paper comprehensively analyzes the mechanism of carbon sink capacity of mariculture in China from five factors: aquaculture structure, aquaculture efficiency, aquaculture scale, competitiveness of shellfish and algae and aquaculture mode. The results show that: (i) the carbon sink of mariculture in China has increased year by year from 2010 to 2019, with obvious heterogeneous spatial distribution characteristics in three marine economic zone. (ii) The improvement of aquaculture efficiency and innovation of aquaculture model contribute the most to the increase of carbon sink, and technological progress plays an increasingly important role. (iii) The weak competitiveness of shellfish and algae seriously hinders the growth rate of carbon sink, and is the main reason for the increasing tightening of carbon sink space. (iv) Regional heterogeneity analysis shows that the mechanism of increasing carbon sink in marine aquaculture is regionally heterogeneous and resource-dependent. Based on these findings, strategies are proposed to emphasize the ecological values of marine aquaculture, accelerate the technological innovation of deep-sea marine aquaculture, improve the organizational system and the management level, and expand the space for marine carbon sink.